Saudi Arabia and Iran : Soft Power Rivalry in the Middle East - Mabon, Simon (London I.B. Tauris, 2016)
Understanding the great power struggle currently affecting the whole of the Middle East.
Include Index, Bibliography and Notes
Library of modern Middle East studies, 132
Keywords: Iran -- Saudi Arabia -- Middle East